Experiencing antipsychotic discontinuation: results from a survey of Australian consumers. Issue 10 (9th October 2014) - Salomon, C.; Hamilton, B.; Elsom, S.
<x xml:space="preserve">Abstract</x> Accessible summary The aim of the survey was to gain an understanding of consumer experiences of antipsychotic discontinuation. Incorporating consumer perspectives into practice may help clinicians to better understand discontinuation decisions and experiences. This topic may be of particular interest to mental health nurses who play an important role in supporting consumers with medication related decisions. The survey highlighted that consumers often try to discontinue antipsychotic medication, frequently without the knowledge or against the advice of clinicians. Consumers who discontinued in such unsupported ways appeared more likely to stop abruptly. Abrupt cessation has been associated with a number of increased risks in the literature. Negative discontinuation symptoms such as difficulty sleeping, mood changes, problems concentrating, increased psychotic experiences and physical problems were reported by more than half of the survey participants. Many consumers reported that they did not feel adequately informed about how to most safely stop or what to expect when stopping. These findings add new knowledge to our understanding of why consumers discontinue antipsychotics. The problems participants reported in their relationship with clinicians, in particular, helps to explain why so many consumers may stop in secret. The need to improve communication between consumers and clinicians around the common experience of antipsychotic discontinuation is highlighted. Findings also highlight the need to conduct further research into discontinuation symptoms and how clinicians might better educate and support consumers who are experiencing them. Abstract Despite high reported rates of antipsychotic non‐adherence, little is known about consumer experiences during discontinuation. This study was designed to increase understanding of antipsychotic discontinuation from consumer perspectives. In 2011–2012, 98 Australian consumers involved with participating organizations completed an anonymous survey detailing past antipsychotic discontinuation attempts. Of the 88 participants who reported at least one discontinuation attempt, over half (n = 47, 54.7%) reported stopping without clinician knowledge or support. This group was 35% (confidence interval 15.4–54.6%) more likely to stop abruptly than those (n = 41, 45.3%) stopping with clinician support (P = 0.002). Only 10 participants (23.3%) recalled being given information about discontinuation symptoms other than relapse; however, 68 participants (78.2%) reported experiencing a range of discontinuation symptoms including physical, cognitive, emotional, psychotic or sleep‐related disturbances. Findings cannot be readily generalized because of sampling constraints. However, the significant number of participants who reported discontinuation symptoms, in addition to psychosis, is consistent with previous research. This study provides new insight into consumer motivations for discontinuation and possible problems in clinical communication that may contribute to frequent non‐collaborative discontinuation attempts. Mental health nurses, who play a pivotal role in medication communication events, may benefit from increased awareness of consumer perspectives on this topic.